(3OjhGf CSGeI Hf efbPs - (3CHhGdeXaQ CSGeI Hf eQTO Hf Ydj Hf ebdO Hf fUQ Hf efbP GdcfGfj GdcdHjs
(3ChdgG (B:s
(3aEfj ZQHJ HfXe GdTYQ aj ZQI GdYeQ adeG YdJ Sfj CcHQJ NWFj hCYXeJg, afOeJ Ydi JaQjWj ajeG fXeJg aMGhdJ Cf CZSd s
(3BNQgG (B:s
(3jfJgj CKfGA bGajI GdgGA Hbhdg(B: (3hbGd HMeU(B: (3jGbdH QabkG HeG CHbjJ ef LdOj ce PG GdMfjf Edi ef CfJ eKhGg s
(3GfXQ GdLRA GdChd Qbe (B284 (3COHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B26 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B775s
(3eUOQ GbJfGA GdCUd (B:s
(3cJHNGfI eLdS ThQGj (B((3WHGWHGFj (B322) s
Keywords: (3GdCOHs